Transformation of Toronipa beach tourism: Valuation and exploring the socio-economic factors on tourist attraction - Anggraini, Yuyun; Sapriyadi, Sapriyadi; Zizih, Andi Rezah Tenri (Universitas Ahmad Dahlan, 2025)
Toronipa beach is one of the famous marine tourism destinations in Southeast Sulawesi, particularly in Konawe. With its beautiful natural potential and relatively straightforward accessibility, Toronipa Beach attracts many local and out-of-town tourists. However, this region has not fully realized its economic potential. To facilitate the decision-making process for its management and development, Economic valuation is very much needed. This study was carried out to estimate the economic value of Toronipa Beach and to identify the socioeconomic factors that influence the number of tourist visits. This study uses the individual travel cost method as an analytical approach and multiple linier regression. The findings indicate that the economic value estimation of Toronipa beach tourism using the individual travel cost method results in an economic value estimate of Rp 75.280.509.614,00 with a consumer surplus value per individual of Rp 450.000,00 per year. According to socio-economic factors that travel costs are inelastic even though the parameter elasticity value is less than 3% and visitor income is positive indicates that visits to Toronipa beach is negative inferior, means that income increases demand to Toronipa beach will increase. The implication of the study that accessibility can be improved by lowering the cost of renting tourist facilities, which can reduce the cost of tourist travel.